A sorceress comes to call - Kingfisher, T. (Tor, Tor Publishing Group, 2024)
"From New York Times bestselling and Hugo Award-winning author T. Kingfisher comes A Sorceress Comes to Call--a dark reimagining of the Brothers Grimm's "The Goose Girl," rife with secrets, murder, and forbidden magic. *The hardcover edition features a foil stamp on the casing and custom endpapers illustrated by the author.* Cordelia knows her mother is . . . unusual. Their house doesn't have any doors between rooms--there are no secrets in this house--and her mother doesn't allow Cordelia to have a single friend. Unless you count Falada, her mother's beautiful white horse. The only time Cordelia feels truly free is on her daily rides with him. But more than simple eccentricity sets her mother apart. Other mothers don't force their daughters to be silent and motionless for hours, sometimes days, on end. Other mothers aren't evil sorcerers. When her mother unexpectedly moves them into the manor home of a wealthy older Squire and his kind but keen-eyed sister, Hester, Cordelia knows this welcoming pair are to be her mother's next victims. But Cordelia feels at home for the very first time among these people, and as her mother's plans darken, she must decide how to face the woman who raised her to save the people who have become like family." --